ANALISIS AKURASI MODEL ALTMAN, GROVER, SPRINGATE, ZMIJEWSKI DALAM MEMPREDIKSI KONDISI FINANCIAL DISTRESS (STUDI EMPIRIS PADA PERUSAHAAN RITEL YANG TERDAFTAR DI BURSA EFEK INDONESIA - SEMBIRING, SABETH; SINAGA, HERMY WATY CRISTINA (Jurnal Riset Akuntansi & Keuangan, 2022)
This study aims to determine which model is the most accurate for predicting financial distress conditions in retail companies listed on the Indonesia Stock Exchange for the 2016-2018 period. The formulation of the problem in this study is whether the Altman method is more accurate in predicting financial distress than the Grover, Springate, and Zmijewski on retail companies listed on the IDX in 2016-2018?” The sample collection technique used is purposive sampling at retail companies with a total sample of 19 companies. Data obtained from the Indonesia Stock Exchange in 2016-2018. The data analysis technique uses the Altman, Grover, Springate and Zmijewski models. The data is analyzed using the calculation of the accuracy level of each model to be able to predict companies experiencing financial distress. The results of this study indicate that there is a difference between the Altman, Grover, Springate and Zmijewski models in predicting financial distress in retail companies listed on the Indonesia Stock Exchange, and the highest level of accuracy is the Springate model with an accuracy rate of 79%.